A factorial randomized controlled trial to evaluate the effect of micronutrients supplementation and regular aerobic exercise on maternal endothelium-dependent vasodilatation and oxidative stress of the newborn (2011)
Background Many studies have suggested a relationship between metabolic abnormalities and impaired fetal growth with the development of non-transmissible chronic diseases in the adulthood. Moreover, it has been proposed that maternal factors such as endothelial function and oxidative stress are key mechanisms of both fetal metabolic alterations and subsequent development of non-transmissible chronic diseases. The objective of this project is to evaluate the effect of micronutrient supplementation and regular aerobic exercise on endothelium-dependent vasodilation maternal and stress oxidative of the newborn. Methods and design 320 pregnant women attending to usual prenatal care in Cali, Colombia will be included in a factorial randomized controlled trial. Women will be assigned to the following intervention groups: 1. Control group: usual prenatal care (PC) and placebo (maltodextrine). 2. Exercise group: PC, placebo and aerobic physical exercise. 3. Micronutrients group: PC and a micronutrients capsule consisting of zinc (30 mg), selenium (70 ?g), vitamin A (400 ?g), alphatocopherol (30 mg), vitamin C (200 mg), and niacin (100 mg). 4. Combined interventions Group: PC, supplementation of micronutrients, and aerobic physical exercise. Anthropometric measures will be taken at the start and at the end of the interventions. Discussion Since in previous studies has been showed that the maternal endothelial function and oxidative stress are related to oxidative stress of the newborn, this study proposes that complementation with micronutrients during pregnancy and/or regular physical exercise can be an early and innovative alternative to strengthen the prevention of chronic diseases in the population.